Progression of hypertension and kidney disease in aging fawn-hooded rats is mediated by enhanced influence of renin-angiotensin system and suppression of nitric oxide system and epoxyeicosanoids - Doleželová, Šárka; Jíchová, Šárka; Husková, Zuzana; Vojtíšková, Alžběta; Kujal, Petr; Hošková, Lenka; Kautzner, Josef; Sadowski, Janusz; Červenka, Luděk; Kopkan, Libor (Clinical and experimental hypertension (New York, N.Y., 2016)
The fawn-hooded hypertensive (FHH) rat serves as a genetic model of spontaneous hypertension associated with glomerular hyperfiltration and proteinuria. However, the knowledge of the natural course of hypertension and kidney disease in FHH rats remains fragmentary and the underlying pathophysiological mechanisms are unclear. In this study, over the animals' lifetime, we followed the survival rate, blood pressure (telemetry), indices of kidney damage, the activity of renin-angiotensin (RAS) and nitric oxide (NO) systems, and CYP450-epoxygenase products (EETs). Compared to normotensive controls, no elevation of plasma and renal RAS was observed in prehypertensive and hypertensive FHH rats; however, RAS inhibition significantly reduced systolic blood pressure (137 ± 9 to 116 ± 8, and 159 ± 8 to 126 ± 4 mmHg, respectively) and proteinuria (62 ± 2 to 37 ± 3, and 132 ± 8 to 87 ± 5 mg/day, respectively). Moreover, pharmacological RAS inhibition reduced angiotensin (ANG) II and increased ANG 1-7 in the kidney and thereby may have delayed the progression of kidney disease. Furthermore, renal NO and EETs declined in the aging FHH rats but not in the control strain. The present results, especially the demonstration of exaggerated vascular responsiveness to ANG II, indicate that RAS may contribute to the development of hypertension and kidney disease in FHH rats. The activity of factors opposing the development of hypertension and protecting the kidney declined with age in this model. Therefore, therapeutic enhancement of this activity besides RAS inhibition could be attempted in the therapy of human hypertension associated with kidney disease.
Keywords: hypertenze; Male; Cytochrome P-450 Enzyme System; Proteinuria; Kidney Glomerulus; stárnutí; proteinurie; Animals; chronic kidney disease; oxid dusnatý; Renin-Angiotensin System; antihypertenziva; Kidney Diseases; Antihypertensive Agents; krevní tlak; Nitric Oxide; glomerulus; Angiotensin-Converting Enzyme Inhibitors; systém (enzymů) cytochromů P-450; mužské pohlaví; Disease Progression; krysa rodu Rattus; Blood Pressure; Aging; modely nemocí na zvířatech; Rats; hypertension; zvířata; Angiotensin II; nemoci ledvin; fawn-hooded rat; proteinuria; progrese nemoci; inhibitory ACE; renin-angiotensin systém; Hypertension; Disease Models, Animal